Penentuan Harga Pokok Produksi Menggunakan Metode Full Costing Pada Produk Berbahan Dasar Limbah Plastik Ecobrick - Octoberry Julyanto; Mira Nurhikmat; Ayu Puspa Wirani; Dewi Anggraini (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The production of plastic waste is increasing every day along with the increase in the number of products and people's consumption patterns. What must be done to overcome the increasing volume of waste is to reduce the volume of waste from the source through community empowerment. Based on Law no. 18/2018 one of the activities for waste management is recycling it into something useful. Ecobricks are one of the creative businesses that can be done. Ecobricks are made from used mineral water bottles filled with plastic waste until they have a solid texture. Products made from ecobricks can be created in the form of chairs, tables, pots and other art items. This potential must be accompanied by the community's ability to determine the selling price or cost of production of the product. In this research, product price determination was calculated using the full costing method for products made from ecobrick plastic waste. The results of price calculations using the full costing method show that the cost of production for each unit of ecobrick creation table is IDR 393,500. In this way, we can know the cost of production that is spent on producing the ecobrick creation table, so that the management can determine the selling price based on the amount of margin they set.